Sile reactions in organic synthesis : - Dorwald, F. Zaragoza (Wiley-VCH, 2005)
Most syntheses in the chemical research laboratory fail and usually require several attempts before proceeding satisfactorily. Failed syntheses are not only discouraging and frustrating, but also cost a lot of time and money. Many failures may, however, be avoided by understanding the structure-reactivity relationship of organic compounds. This textbook highlights the competing processes and limitations of the most important reactions used in organic synthesis. By allowing chemists to quickly recognize potential problems this book will help to improve their efficiency and success-rate. A must for every graduate student but also for every chemist in industry and academia